2022
DOI: 10.18488/73.v10i2.2959
|View full text |Cite
|
Sign up to set email alerts
|

Risk Management Disclosure and their Effect on Banking Firms Value in Indonesia

Abstract: Risk management is the effort done to minimize the possible risks that might occur in future. This study aimed to examine the influence of firm size, audit committee, and risk committee on risk management disclosure and to examine the influence of firm size, audit committee, risk committee, and risk management disclosure on firm banking value. The research sample comprised 40 banking firms listed on the Indonesia Stock Exchange (IDX) during 2016 to 2018. The hypothesis testing was done by using a regression da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…However, this methodology presents an increase to the size existing residual income, which is defined as operating profit minus capital charge. Mathematically EVA gives the same result in scoring as Discounted Cash Flow (DCF) or Net Present Value (NPV), which has long been widely recognized as the best theoretical analytical tool from a shareholder perspective (Eugster and Wagner, 2020); Rahayu et al, 2022;Sharma et al, 2022. The definition given by Stern Value Management to EVA shows that EVA is the difference between a business organization's net operating profit after tax and the cost of capital opportunities invested in business organizations (Jakub et al, 2015). The following the formula for EVA.…”
Section: Economic Value Added (Eva)mentioning
confidence: 99%
“…However, this methodology presents an increase to the size existing residual income, which is defined as operating profit minus capital charge. Mathematically EVA gives the same result in scoring as Discounted Cash Flow (DCF) or Net Present Value (NPV), which has long been widely recognized as the best theoretical analytical tool from a shareholder perspective (Eugster and Wagner, 2020); Rahayu et al, 2022;Sharma et al, 2022. The definition given by Stern Value Management to EVA shows that EVA is the difference between a business organization's net operating profit after tax and the cost of capital opportunities invested in business organizations (Jakub et al, 2015). The following the formula for EVA.…”
Section: Economic Value Added (Eva)mentioning
confidence: 99%
“…There is a large body of literature examining the various factors that affect environmental performance, which encompasses a wide range of aspects, including economic, social, political, technological, and natural factors. A review of this literature highlights several key factors that are commonly seen as having the greatest impact on environmental performance (Kirikkaleli et al, 2021;Noh, 2010;Sadorsky, 2010;Chi et al, 2021;David and Venkatachalam, 2018;Tolliver et al, 2019;Ali et al, 2014;Rahayu et al, 2022;Sharma et al, 2022;Mubeen et al, 2022). In recent years, the issue of environmental sustainability has gained increasing attention from policymakers, financial institutions, and the general public.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Under the influence of the media, managers can effectively reduce the violations of managers' self-interest trends. Rahayu et al (2022) concluded that negative media reports will inhibit managers' desire to satisfy their interests and play a role in enterprise governance. In summary, this paper proposes the following hypothesis H2b: Hypothesis H2b: Negative media reports can inhibit overinvestment caused by managers' overconfidence.…”
Section: Moderating Effect Of Media Reports On Managers' Overconfiden...mentioning
confidence: 99%